Dramatic size effects and evidence of structural isomers in the reactions of rhodium clusters, Rhn+/-, with nitrous oxide - Harding, D; Ford, M; Walsh, T; Mackenzie, S (Royal Society of Chemistry, 2007)
The reactions of gas phase rhodium clusters, Rhn+/- (n<30), with nitrous oxide, N2O, have been investigated under single collision conditions by Fourier transform ion cyclotron resonance mass spectrometry. The only significant reaction observed is the sequential generation of oxides. Absolute rate constants for the reactions of all clusters have been determined and, in the case of the cationic clusters especially, they exhibit large fluctuations as a function of cluster size with local minima observed for n=5, 19, 28. Striking similarities are observed with the variation in rate constants for these clusters in reactions with small hydrocarbons (C. Adlhart and E. Uggerud, J. Chem. Phys., 2005, 123, 214709). Corresponding size effects are also observed but are less marked in the reactions of the anionic clusters. The reactions of several clusters exhibit marked deviations from simple pseudo-first-order kinetics suggesting the presence of multiple isomeric forms: Rh11+, Rh12+ and Rh8- exhibit characteristic biexponential decays which are interpreted in terms of the existence of different structural forms of the cluster which have markedly different reactivity. By contrast, Rh6+, Rh7+ and Rh8+ show rates which apparently increase with time, probably due to collisional activation. Thermalisation of the clusters prior to reaction by exposure to pulses of argon results in changes to the kinetics of these anomalous systems which can be explained in terms of collision induced isomerisation.